2014
DOI: 10.3892/ijmm.2014.1861
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits human retinal pigment epithelial cell proliferation

Abstract: Proliferative vitreoretinopathy (PVR) is a common cause of intraoperative failure following retinal reattachment surgery and is mediated in part through the migration, de-differentiation and proliferation of retinal pigment epithelial (RPE) cells. Given the cytotoxic effects of curcumin on epithelial and endothelial cells, in this study, we assessed the effects of curcumin on human RPE (hRPE) cell proliferation. WST-1 analysis revealed that curcumin significantly inhibited primary hRPE cell proliferation in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Curcumin is a monomer component from traditional Chinese medicine that exhibits anti-proliferation, anti-tumor, and anti-inflammatory effects, among others [8,9]. Previous studies show that curcumin can inhibit RPE cell proliferation in vitro [10,11]; however, there are no reports on whether this inhibition is achieved by downregulating EGF expression. In the current study, different concentrations of curcumin were used to treat RPE cells cultured in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin is a monomer component from traditional Chinese medicine that exhibits anti-proliferation, anti-tumor, and anti-inflammatory effects, among others [8,9]. Previous studies show that curcumin can inhibit RPE cell proliferation in vitro [10,11]; however, there are no reports on whether this inhibition is achieved by downregulating EGF expression. In the current study, different concentrations of curcumin were used to treat RPE cells cultured in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, curcumin has many benefits, such as a high level of safety, low toxicity, a wide range of treatment uses, and low cost. Curcumin also inhibits RPE cell proliferation [10][11][12], although it is unknown whether it plays an important role in the prevention of PVR formation. However, curcumin has been reported to regulate the biological functions of EGF, which plays important roles in the development of PVR.…”
Section: Introductionmentioning
confidence: 99%
“…NORFLO is a curcumin-phosphatidylcholine complex (iphytoone) with recently described anti-inflammatory properties. 7 10 Although the mechanism is yet to be fully elucidated, several studies reported the beneficial effects of curcumin in many relapsing ophthalmic diseases sustained by long-standing inflammation such as central serous chorioretinopathy, diabetic retinopathy, dry eye, and uveitis of different etiologies. 11 –13,25 –29 In the present series, we reported an improvement of chronic 1+ anterior chamber flare after a 1 year course of oral therapy with NORFLO tablets.…”
Section: Discussionmentioning
confidence: 99%
“…1b). Curcumin (15 μM) treatment of RPE cells was previously shown to arrest cell cycle progression with arrest in the G1 phase [12]. Cell cycle progression of ARPE-19 cells exposed to 0-50 μM nano-curcumin did not show significant changes in cell proliferation (Fig.…”
Section: Nano-curcumin Is Not Cytotoxic For Arpe-19 Cells Unlike Curmentioning
confidence: 94%